Structural changes in the Swedish economy - Östblom, Göran (Stockholm University, 2026)
This survey is an attempt to exploit systematically information about past changes in the Swedish production structure gained from input-output investigations for the years 1957, 1968, 1975 and 1980. Imported and domestically produced intermediates measured in 1968 prices. The data files consists of coefficient matrices for the years 1957, 1968, 1975 and 1980 for 26 commodity groups and 72 commodity groups respectively.

Denna undersökning är ett försök att systematiskt utnyttja information om tidigare förändringar i den svenska produktionsstrukturen, baserad på input–output-undersökningar för åren 1957, 1968, 1975 och 1980. Importerade och inhemskt producerade insatsvaror är mätta i 1968 års priser. Datafilerna består av koefficientmatriser för åren 1957, 1968, 1975 och 1980, för 26 respektive 72 varugrupper.
Strukturell förändring i svensk ekonomi
Keywords: Economic policy, public expenditure and revenue; Ekonomisk politik, offentliga utgifter och intäkter; Economic systems and development; Ekonomiska system och ekonomisk utveckling; Social Sciences; Samhällsvetenskap; Economics and Business; Ekonomi och näringsliv